(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. Evidence demonstrates that cardiovascular risk reduces after kidney transplantation, but is still a major cause of death. With increasing inclusion of diabetic patients for kidney transplantation, the evaluation of cardiovascular disease in this population becomes more important. We compared arterial stiffness and pulse wave reflection as well as other cardiovascular risk factors in kidney transplant patients with and without diabetes mellitus. Materials and Methods. One hundred kidney transplant recipients, including 33 diabetic patients, were evaluated for their renal-cardiovascular risk factors, including blood pressure, lipids, glucose control, homocysteine, and arterial stiffness indexes. The tests were repeated after 1 year in 47 individuals. Results. There was no significant difference in pulse wave velocity (PWV) between the diabetic and nondiabetic groups, despite a greater augmentation index (AI) in the diabetic group (20.5 ± 2.3 versus 13.1 ± 2.2). Multivariable analysis revealed that diabetes mellitus was a significant determinant for AI independently of age, blood pressure, posttransplant time, gender, and glomerular filtration rate (R2 = 39%). Repeated test after 1 year demonstrated a significant reduction in the carotid-femoral PWV (P = .03) and systolic blood pressure (P = .007). Conclusions. In contrast to nontransplant groups, AI was significantly greater in diabetic kidney transplant patients compared to their nondiabetic counterparts, despite a comparable PWV. However, carotid-femoral PWV improved after 1 year. These may reflect progressive ventricular and large arterial function improvement despite remained small arterial defects after transplantation. It also suggests potential role of arterial evaluation in risk assessment among kidney transplant patients.